Update of the list of QPS‐recommended biological agents intentionally added to food or feed as notified to EFSA 6: suitability of taxonomic units notified to EFSA until March 2017. (25th July 2017) - ,; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Girones, Rosina; Koutsoumanis, Kostas; Lindqvist, Roland; Nørrung, Birgit; Robertson, Lucy; Ru, Giuseppe; et al.
Abstract: The qualified presumption of safety (QPS) concept was developed to provide a harmonised generic pre‐evaluation to support safety risk assessments of biological agents performed by EFSA's scientific Panels. The identity, body of knowledge, safety concerns and antimicrobial resistance of valid taxonomic units were assessed. Safety concerns identified for a taxonomic unit are, where possible and reasonable in number, reflected as 'qualifications' which should be assessed at the strain level by the EFSA's scientific Panels. No new information was found that would change the previously recommended QPS taxonomic units and their qualifications. Between the end of September 2016 and March 2017, the QPS notification list was updated with 87 applications for market authorisation. From these, 32 biological agents already had a QPS status, and 37 were not included in the evaluation as they are filamentous fungi or enterococci. Streptomyces species ( Streptomyces   cinnamonensis, Streptomyces mobaraensis and Streptomyces   violaceoruber), Bacillus circulans (three notifications) and Escherichia coli (seven notifications) were re‐confirmed not suitable for QPS. Streptomyces rubiginosus and Streptomyces   netropsis, not evaluated within the previous mandate, were also not recommended for QPS. Streptomyces spp. and  E. coli will be excluded from further QPS evaluations within the current QPS mandate. Hyphomicrobium denitrificans, which has never been evaluated before, was not recommended for the QPS list and for Pseudomonas amyloderamosa, the QPS assessment was not applicable because it is not a validated species. Lactobacillus animalis was a new taxonomic unit recommended to have the QPS status.